Occurrence of insect pests and loss caused by them in 'UPAS 120' pigeonpea (Cajanus cajan) in western plains zone of Uttar Pradesh - Chaudhari, R R P; Sachan, R B (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1988 and 1989 to observe the occurrence of insect species at various growth stages and loss caused by them on the seed yield of 'UPAS 120' pigeonpea [Cajanus cajan (L.) Millsp.]. The insect fauna was recorded during both the years. Endosulfan 35 EC 0.07% spray during vegetative to pre-maturity stage of the crop gave the least pod damage (7.37%) and highest seed yield (1624 kg/ha). The crop protected only at active vegetative growth stage did neither increase the seed yield nor significantly reduce the infestation of the complex, consisting of pigeonpea podfly (Melanagromyza obtusa Malloch), gram podborer [Helicoverpa armigera (Hubner)], cowpea podboror [Maruca testulalls (Geyer)] and pigeonpea phume moth (Exeiastis atomsa Walshingham). Endosulfan spray at reproductive stage of the crop effectively reduced the pod damage, giving significant increase in seed yield and maximum economic return compared with the control.